Public reporting of antipsychotic prescribing in nursing homes: population-based interrupted time series analyses - Ivers, Noah M; Taljaard, Monica; Giannakeas, Vasily; Reis, Catherine; Williams, Evelyn; Bronskill, Susan (BMJ quality & safety, 2019)
BackgroundAlthough sometimes appropriate, antipsychotic medications are associated with increased risk of significant adverse events. In 2014, a series of newspaper articles describing high prescribing rates in nursing homes in Ontario, Canada, garnered substantial interest. Subsequently, an online public reporting initiative with home-level data was launched. We examined the impact of these public reporting interventions on antipsychotic prescribing in nursing homes.MethodsTime series analysis of all nursing home residents in Ontario, Canada, between 1 October 2013 and 31 March 2016. The primary outcome was the proportion of residents prescribed antipsychotics each month. Balance measures were prescriptions for common alternative sedating agents (benzodiazepines and/or trazodone). We used segmented regression to assess the effects on prescription trends of the newspaper articles and the online home-level public reporting initiative.ResultsWe included 120 009 nursing home resident admissions across 636 nursing homes. Following the newspaper articles, the proportion of residents prescribed an antipsychotic decreased by 1.28% (95% CI 1.08% to 1.48%) and continued to decrease at a rate of 0.2% per month (95% CI 0.16% to 0.24%). The online public reporting initiative did not alter this trend. Over 3 years, there was a net absolute reduction in antipsychotic prescribing of 6.0% (95% CI 5.1% to 6.9%). Trends for benzodiazepine prescribing did not change as substantially during the period of observation. Trazodone use has been gradually increasing, but its use did not change abruptly at the time of the mass media report or the public reporting initiative.InterpretationThe rapid impact of mass media on prescribing suggests both an opportunity to use this approach to invoke change and a warning to ensure that such reporting occurs responsibly.